Do poder à família na aula imperial: imagens da morte nas obras as Troianas e Agamêmnon de Sêneca (01 a.C. 65 d.C.) - Carneiro, Douglas de Castro (2021)
In this thesis, we investigated the representations of death in the plays Troades and Agamemnon by Seneca (01 B.C. - 65 A.D.), written between Claudius and Nero principalities (41 A.D. - 68 A.D.). The justification of this study is mainly centered on the influence of Greek mythology on the Roman world. And the war as a part of the political imaginary. Our general aim is to understand how Seneca thinks the family relationships in the mortuary context in the Trojan cycles’ tragedies. The specific aims are: to identify the family images in the tragedies Troades and Agamemnon; to understand death in the Trojan cycle as well as to conceptualize death (murders, sacrifices, funeral rites, suicides and social death); to understand the emotional dimensions and attitudes of characters played in the respective tragedies; to understand the Seneca’s reflections on death and family relationships in the context of the imperial Aula. For such, we suggested two main hypotheses: Seneca wrote the tragedies Troades and Agamemnon recurring to Greek archetypes to adapt them to the context of the Paideia Latina because, as we suppose, he aimed at instructing aristocratic groups. In both tragedies, his reflections alluded to the nature of political power, especially to the abusive behaviors of these public men, such as king Agamemnon. In this sense, our second hypothesis relates to the abusive power in spaces of political power. So, attempting to formulate a new behavioral esthetic, Troades and Agamemnon delivery to readers-listeners war landscapes related to the images of death and family in the Empire Court. According to our proposition, the stoical practice should control death and family on the domestic core because public and private spaces intertwine in the Roman Mediterranean. The rex’s deviant behavior induces disturbances in the power exercise; therefore, in the tragedies and even in his treaties (e.g., De Clementia), the philosopher uses the image of death, a threshold situation, to emphasize that even in a sign of loss, caused by death or by war, citizens should control his emotions. Thus, we suppose that the citizen’s conduct on the social space of death and family was directly integrated into the political scenario; ergo, the maintenance of the Res Publica. In any case, our research entered a not yet clear debate: family and death in their social relations in light of the Seneca’s tragedies. Such representations are conflicting and lead this research to a fair accomplishment.